Immune Response to Capsular Polysaccharide of Streptococcus pneumoniae in Rabbits Immunized with Pneumococcal Conjugate Vaccine - Zaenab; Tafroji, Wisnu; Salsabila, Korrie; Winarti, Yayah; Wulandari, I Gusti Ayu Inten; Yasmon, Andi; Safari, Dodi (Bogor Agricultural University, Indonesia, 2025)
To evaluate the immune response of a rabbit model to polysaccharide capsules of Streptococcus pneumoniae after primary and booster immunization with pneumococcal conjugate vaccine. Rabbits were immunized with 0.25 ml of the 13-valent pneumococcal conjugate vaccine (PCV13) on Day 0, 7, and 14. Blood of rabbits was collected to measure the specific antibodies against the native polysaccharide capsules of S. pneumoniae serotypes 6B (Anti-Pn6BPS antibodies) and 19F (Anti-19FPS antibodies) using enzyme-linked immunosorbent assay (ELISA). The specific anti-Pn6BPS and anti-Pn19FPS antibodies in the immunized group increased significantly compared to the control rabbit after immunization (P<0.05). The highest titer of anti-Pn6BPS and anti-Pn19FPS antibodies were obtained on Day 21 and Day 28, respectively. The third immunization on Day 21 is a fairly high increase in specific antibodies against polysaccharide type 6B and type 19F. The highest antibody titers against polysaccharide capsules of S. pneumoniae were obtained after booster immunization.